God in early Christian thought : essays in memory of Lloyd G. Patterson - Patterson, L. G. 1929-1999.; McGowan, Andrew Brian, 1961-; Daley, Brian, 1940-; Gaden, Timothy J. (Vigiliae Christianae, Supplements, 2009)
While the diversity of early Christian thought and practice is now generally assumed, and the experiences and beliefs of Christians beyond the works of great theologians increasingly valued, the question of God is perennial and fundamental. These essays, individually modest in scope, seek to address that largest of questions using particular issues and problems, or single thinkers and distinct texts. They include studies of doctrine and theology as traditionally conceived, but also of understandings of God among the early Christians that emerge from study of liturgy, art, and asceticism, and in relation to the social order and to nature itself.